An examination of cultural elements in music curricula of selected private secondary Schools in Lagos State - Ojelabi, Olufemi Ojelabi (Obafemi Awolowo University, 2019)
This Study traced the origin and development of music curricula in Nigerian secondary school. It examined the concept of the music curricula of private secondary schools in Lagos State and established the philosophical bases on which the curricula were premised. It also indentified and assessed the level of infusion of cultural elements in the curricula. This was with a view to explicating the effectiveness of the curricula of the private secondary schools in Nigeria, using Lagos state a case study. The study employed a survey method using questionnaire to elicit information on the operations of the curricula used in selected private secondary schools in Lagos State. Twenty private secondary schools were purposively selected for the study. One school was chosen from each of the twenty Local Government Areas. Proprietors / Proprietresses, Principals and two Music teachers of each of the selected schools were interviewed. Two different research instruments were developed and administered; these were the oral interview and questionnaire tagged. “Questionnaire on Music Curriculum” (QMC). The instruments were personally administered on music teachers, schools principals, proprietors as well as students of the selected schools in each of the selected Local Government Areas. Data collected were analyzed statistically using T-test calculation at 0.05 level of significance. The results showed that there were slight differences in the curricula used at private secondary schools in Lagos State. It was observed that European influence was prominent in the curricula as reflected in their schemes of works. It was also discovered that Music teachers in private secondary schools were not involved in the planning stage of the Music Curricula. It was also noted that Nigeria local musical instruments were not seen in many schools despite the fact that the curriculum stipulated the teaching of such instruments. Furthermore, it was revealed that there was no clear philosophy as regards the music curricula of Nigerian Private Secondary Schools. The result also showed that Cultural dances and indigenous music were either seldomly taught or not taught at all in the school under discourse. The study concluded that philosophy of Music Curricula of most private secondary schools in Lagos, Nigeria, as designed by Europeans during the colonial era was Eurocentric and less relevant to the socio-cultural activities of Nigerian people.